2017
DOI: 10.1371/journal.pone.0174822
|View full text |Cite
|
Sign up to set email alerts
|

Discover cervical disc arthroplasty versus anterior cervical discectomy and fusion in symptomatic cervical disc diseases: A meta-analysis

Abstract: ObjectiveSymptomatic cervical disc disease (SCDD) is a common degenerative disease, and Discover artificial cervical disc, a new-generation nonconstrained artificial disk, has been developed and performed gradually to treat it. We performed this meta-analysis to compare the efficacy and safety between Discover cervical disc arthroplasty (DCDA) and anterior cervical discectomy and fusion (ACDF) for SCDD.MethodsAn exhaustive literature search of PubMed, EMBASE, and the Cochrane Library was conducted to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
2
14
0
1
Order By: Relevance
“…It is worth pointing out that the frequency of postoperative dysphagia/dysphonia was significantly lower in patients with mobile devices, which is at variance with the study published last year 36. Both the number of secondary surgical interventions at the index level and adverse events (excluding dysphagia/dysphonia) in CDA and ACDF groups were not statistically different, in agreement with the results of the previous studies 6,11,26,36,41. This is interesting because the previous generations of CDA prostheses (such as Bristol-Cummins) were known to cause subluxation, screw damage, and dysphagia 42.…”
Section: Discussionsupporting
confidence: 83%
“…It is worth pointing out that the frequency of postoperative dysphagia/dysphonia was significantly lower in patients with mobile devices, which is at variance with the study published last year 36. Both the number of secondary surgical interventions at the index level and adverse events (excluding dysphagia/dysphonia) in CDA and ACDF groups were not statistically different, in agreement with the results of the previous studies 6,11,26,36,41. This is interesting because the previous generations of CDA prostheses (such as Bristol-Cummins) were known to cause subluxation, screw damage, and dysphagia 42.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, in our study, the results of subgroup analysis demonstrated that the difference in secondary surgery at the index level was not statistically significant between the two treatments in Bryan, Discover, and Kineflexl/C prosthesis groups. However, the number of studies included was not large enough, and more studies are needed in future analyses.…”
Section: Discussionsupporting
confidence: 90%
“…Выполненный метаанализ проспективных рандомизированных исследований не выявил различий в распространенности нежелательных явлений в исследуемых группах пациентов. полученные нами данные согласуются с результатами метаанализов S. Lei с соавторами [27], S. Yi с соавторами [28] и M. Qi с соавторами [29]. Отметим, что наиболее распространенным нежелательным явлением и в обеих группах пациентов являлась дисфагия.…”
Section: Discussionunclassified